Design, optimisation, in vitro and in vivo evaluation of promising once-a-day tablet formulations of the novel antihypertensive drug MT-1207 - Vrettos, Napoleon Nikolaos (2022)
Hypertension is the most common cardiovascular disease characterised by elevated systolic and diastolic blood pressure. Globally, around 1.28 billion adults have hypertension with only about 21 % having it under control. Prevalence depends on a range of different factors. Currently, there are many different drugs that are used to manage hypertension through different mechanisms of action. In recent years, guidelines suggest that hypertension should be treated with a combinatory therapy from its onset, instead of monotherapy, so that many different receptors can be targeted. However, the administration of many different drugs to hypertensive patients (polypharmacy) can in itself impede patient compliance to the treatment, reducing the desired effectiveness of this approach.